DEVELOPMENT OF MATHEMATICAL CONCEPTS OF PRESCHOOL CHILDREN - Jomurodova Nilufar Tulqin qiz, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In the article, different methods of approach to learning geometric shapes of children of different ages are studied. How to approach each child as an individual, how to distinguish shapes and how to teach them is explained. Children are divided into four groups.